2020
DOI: 10.21203/rs.3.rs-52778/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pilot Trial of High-dose vitamin C in critically ill COVID-19 patients

Abstract: Background: No specific medication has been proven effective for the treatment of patients with severe coronavirus disease 2019 (COVID-19). Here, we tested whether high-dose vitamin C infusion was effective for severe COVID-19.Methods: This randomized, controlled, clinical trial was performed at 3 hospitals in Hubei, China. Patients with confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the ICU were randomly assigned in as 1:1 ratio to either the high-dose intravenous vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(88 citation statements)
references
References 31 publications
0
88
0
Order By: Relevance
“…It is worthy to note that some studies have used higher doses of vitamin C in their patients [39,40]. The highest dose was used in the work of Zhang et al who have used 24 g daily in the form of 12 g of vitamin C/50 ml every 12 h for 7 days at a rate of 12 ml/h.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthy to note that some studies have used higher doses of vitamin C in their patients [39,40]. The highest dose was used in the work of Zhang et al who have used 24 g daily in the form of 12 g of vitamin C/50 ml every 12 h for 7 days at a rate of 12 ml/h.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently there were publications reporting clinical benefits of intravenous ascorbate supplementation in critically ill patients with COVID-19. 9,10 However, the mechanisms involved are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the same authors reported in a meta-analysis of 12 clinical trials that vitamin C reduces the length of the intensive care unit stay by 7.8% and the duration of mechanical aided ventilation [ 41 , 42 , 43 ]. Emerging evidence, carried out on a small clinical trial with 54 critical COVID-19 patients, demonstrated that high dose vitamin C infusion decreased the IL-6 level, concluding that this therapeutical regimen may provide a protective clinical effect without any adverse events in critical COVID-19 patients [ 44 ]. Other outcomes were considered in the same clinical trial, including organ failure score, intensive care unit length, and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Other outcomes were considered in the same clinical trial, including organ failure score, intensive care unit length, and mortality. According to the authors, a significant decrease in intensive care unit stay and hospital mortality was observed in the vitamin C treated patients [ 44 ]. Overall, vitamin C seemed to possess relevant pharmacological properties against severe respiratory infections, including COVID-19 [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%